Cloning, Sequencing and Expression of the Brucella Melitensis Novel Lomr Protein (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: Brucellosis is a zoonotic infection transmitted from animal to human directly by the animal or indirectlyfrom their products. It is worldwide distribution especially in the middle east including Iraq and KurdistanRegion. Materials and methods: The gene coding for the outer membrane protein assembly factor LomRof 18kDa, now designated of Brucella melitensis 16M was cloned and sequenced. Cloning of insert DNAfrom bacteria into pET-28+ allowed the selection of a plasmid bearing a 5.5-kb NcoI fragment that seemedto contain the entire omp gene under control of its own promoter. Results: LomR was localized within aregion between the NcoI and XhoI insert of approximately 396 bp. The reliability of the constructed plasmidwas established by restriction enzyme mapping and sequencing. LomR was expressed after induction withIPTG in Escherichia coli BL21. Recombinant LomR was purified by chromatography through Ni-agarose.Sequencing of this region revealed an open reading frame of 390 bp encoding a protein of 132 amino acidsand a predicted molecular mass of 20 KDa. Conclusion: The availability of recombinant LomR and theidentification of the antigenic determinant recognized will allow the evaluation of their potential protectiveactivity and their potential for the development of subunit vaccine against brucellosis.
Keywords: (PCR, cloning, LomR, DNA, Gene, Protein, expression, Brucella melitensis)